Bioinformatics analysis of an animal model of diet-induced nonalcoholic fatty liver disease with rapid progression. Issue 3 (February 2022) - Hong, Wei; Zhang, Tingting; Yan, Junbin; Yu, Jianshun; He, Beihui; Wu, Liyan; Yao, Kannan; Mao, Wei; Chen, Zhiyun
Nonalcoholic fatty liver disease (NAFLD) develops rapidly in high-fat diet (HFD) fed Mongolian gerbil ( Meriones unguiculatus ). Here, we aim to explore the gene expression characteristics of Mongolian gerbil to better understand the underlying mechanism in this animal model. Mongolian gerbils were fed with normal diet or HFD for different periods. High-throughput sequencing was carried out on the hepatic mRNA and bioinformatics analysis was further performed. Eight hub genes Cd44, App, Cdc42, Cd68, Cxcr4, Csf1r, Adgre1, and Fermt3, which were involved in inflammation, fibrosis, and HCC were obtained. Four significant independent poor prognostic factors for HCC (GPC1, ARPC1B, DAB2, and CFL1) were screened out. qRT-PCR result showed that the above genes expressed high levels in different periods of modeling process. The findings of this study provide useful information for further studies on Mongolian gerbil NAFLD model.